Development Of Cost-Saving Energy For Home Lighting Based Microcontroller and RTC - Maharmi, Benriwati; Kardova, Toriq; Ermawati (International Journal of Electrical, Energy and Power System Engineering, 2019)
The use of controlled and efficient electrical energy can save the cost of electricity expenditure. This study aims to design the cost saving energy tool for household scale of lighting using automatic microcontroller system. The design of the appliance used the automatic control system of home lights, which setting time using RTC (Real Time Clock) and a microcontroller Arduino Mega 2560. Power supply on this system was operated to supply power all existing components and controller using Arduino Mega 2560 microcontroller. Based on the test results, the cost-saving energy tool worked as an expectation of controlling the On/Off lights automatically, the RTC and current sensors can work properly to limit the current. Therefore, this design proposed can reduce the cost of electrical energy.